Pengaruh Penilaian Kinerja Dan Kompensasi Terhadap Produktivitas Kerja Pada PDAM Kabupaten Karawang - Feriyati Suharto (SMARTINDO, 2023)
This study aims to analyze the effect of performance appraisal and compensation on work productivity. Themethod in this study is a descriptive method in the form of a questionnaire using a sample of 25 people or 35% ofthe total population studied as many as 70 people. The results of the analysis show that the relationship betweenwork appraisal variables and employee work productivity is positive and strong. The relationship between thecompensation variable and employee work productivity is positive and very strong. Simultaneously, there is aneffect of performance appraisal and compensation on employee work productivity. Partially, there is an effect ofperformance appraisal and compensation on employee work productivity.